Plantar Vein Thrombosis Mimicking Tendinopathy. Issue 1 (25th January 2022) - Kubincova, Michaela; Vanhoenacker, Filip
Teaching point : Plantar vein thrombosis is a rare condition that should be considered in the differential diagnosis of ankle pain, particularly in patients with a high clinical index of suspicion for venous thrombosis.